Lactosylceramide in lysosomal storage disorders - a comparative immunohistochemical and biochemical study - Hůlková, Helena; Ledvinová, Jana; Asfaw, Befekadu; Koubek, Kristián; Kopriva, K; Elleder, Milan (Virchows Archiv, 2005)
Immunohistochemical studies of the presence of lactosylceramide (LacCer) in lysosomal storage disorders (LSDs) were done using anti-LacCer monoclonal antibody of the CDw 17 type (clone MG-2). No sign of an association between LacCer and the lysosomal system in normal cells was observed, except for histiocytes active in phagocytosis. A comparative study of a group of LSDs showed a general tendency for LacCer to increase in storage cells in Niemann-Pick disease type C (NPC), and types A and B, GM1 gangliosidosis, acid lipase deficiency, glycogen storage disease type II and mucopolysaccharidoses. LacCer accumulated in storage cells despite normal activity of relevant lysosomal degrading enzymes. The accumulation of LacCer displayed variability within storage cell populations, and was mostly expressed in neurons in NPC. An absence of the increase in LacCer in storage cells above control levels was seen in neuronal ceroid lipofuscinoses (neurons and cardiocytes) and in Fabry disease. Gaucher and Krabbe cells showed significantly lower levels, or even the absence, of LacCer compared with control macrophages. Results of immunohistochemistry were corroborated by semiquantitative lipid thin-layer chromatography (TLC). It is suggested that different associations of LacCer with the lysosomal storage process may reflect differences in glycosphingolipid turnover induced by the storage-compromised lysosomal/endosomal system.
Keywords: Neurons; Financing, Government; makrofágy; Cerebral Cortex; Spleen; laktosylceramidy; dítě; chromatografie na tenké vrstvě; Lactosylceramides; biologické markery; histiocyty; neurony; lyzozomální nemoci z ukládání; mozková kůra; slezina; Lysosomal Storage Diseases; CD antigeny; Adult; Immunohistochemistry; Child; Chromatography, Thin Layer; dospělí; játra; Histiocytes; imunohistochemie; Biomarkers; Liver; Macrophages; financování vládou; Antigens, CD